Perlindungan Hukum Terhadap Warga Negara Keturunan Asia Dari Tindakan Diskriminasi Rasial Di Masa Pandemi Covid 19 - Fikryansha Tuah; Arman Anwar; Richard Marsilio Waas (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The 2019 coronavirus (COVID-19) pandemic has exposed social and political rifts in society, the emergence of racial and discriminatory responses to fear, which disproportionately affects marginalized groups especially those of Asian descent in America and Europe.Purposes of the Research: To study and find out the protection of international law for citizens of Asian descent during the covid 19 pandemic based on the international convetion on the elimination of all form of racial discrimination 1965, and to examine and know the state’s responsibility for acts of racial discrimination for citizens of Asian descent america during the covid 19 pandemic.Methods of the Research: The research method uses normative juridical law research, with primary and secondary legal materials as sources of law. The problem approach used is a conceptual approach. The case approach, and the statute approach. Furthermore, it was analyzed qualitatively.Results of the Research: The results show that the Covid 19 pandemic has increased hate crimes against Asians. The spike in hatred increased because Asians were blamed for the occurrence of Covid 19, which was first identified in Wuhan, China 2019. Protection against acts of racial and ethnic discrimination regulated in the International Convention of the Elimination of All Forms of Racial Discrimination (ICERD) is the elimination of discrimination that must be done immediately and in all its forms and manifestations, including the prevention and eradication of racist doctrines and practices, to promote mutual understanding between races and to build an international community free from all forms of racial exclusion and racial discrimination. States parties undertake to provide, through competent national courts and other national institutions, effective protection and remedies for everyone within their jurisdiction from racial discrimination in violation of the present Covenant, and to fulfill or satisfy the Right to compensation for all form of loss suffered as a result of such discriminatory treatment. States parties are obliged to take all appropriate steps to develop policies as soon as possible to eliminate all forms of racial discrimination and promote understanding between races.